DEVELOPMENT OF MAGNETIC ROULETTE MEDIA BY USING DISCOVERY LEARNING FOR THE INTRODUCTION OF SYMBOLS 1-10 IN CHILDREN AGED 4 - 5 YEARS AT HIDAYATUS SHIBYAN KINDERGARTEN SURABAYA - Bakrisuk, Fidya Salim; Setyowati, Sri; Khotimah, Nurul (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
Activities Based Contemporary (PABC) learning model on gross motor skills, especially balance, and learning concentration in children aged 4-5 years. The background of the study shows that there is a high percentage of children aged 4-5 years at Al Irsyad Kindergarten, Banyuwangi Regency who have less than optimal balance (74.5%) and learning concentration (71.1%). This is identified as one of the reasons for the tendency of children to spend more and more time with passive activities in front of the screen of gadgets. This study uses a quantitative approach with a design that involves statistical tests to measure the influence of PABC. The subjects of the study were children aged 4-5 years at Al Irsyad Kindergarten Banyuwangi. Data were collected through observation using motor ability and concentration observation sheets. Data analysis includes normality tests, homogeneity tests, validity tests, reliability tests, as well as Independent Sample T-Test and Paired Sample T-Test. The PABC model itself is an integration of physical activity with contemporary elements that are relevant to children, emphasizing freedom of movement, self-expression, and the use of games as a fun and effective learning method. Its implementation is manifested in a series of physical obstacles such as